2012
DOI: 10.3141/2279-11
|View full text |Cite
|
Sign up to set email alerts
|

Assessing International Transferability of Highway Safety Manual Crash Prediction Algorithm and Its Components

Abstract: The Highway Safety Manual (HSM) provides an algorithm, and associated knowledge, for predicting crashes for different facility types. This algorithm requires calibration to current local conditions to enhance transferability, using a procedure that is prescribed in the HSM. However, there is no procedure for assessing transferability. To fill this void, this paper is focused on the methodology for assessing the transferability of the key HSM algorithm components, the baseline Safety Performance Function (SPF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 9 publications
0
37
0
4
Order By: Relevance
“…Additionally the impacts of geometric changes, for example, implementation of bus priority lanes [62], could be evaluated using proposed microsimulation method. Also, the proposed method could be utilized to validate existing CMFs for local representation, a validation process recommended by AASHTO [36]. As a result, the practitioners can comfortably transfer the prior developed CMFs and apply those at different problematic regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally the impacts of geometric changes, for example, implementation of bus priority lanes [62], could be evaluated using proposed microsimulation method. Also, the proposed method could be utilized to validate existing CMFs for local representation, a validation process recommended by AASHTO [36]. As a result, the practitioners can comfortably transfer the prior developed CMFs and apply those at different problematic regions.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis Journal of Advanced Transportation 3 method and expert panel survey were also proposed to estimate CMFs [35]. Furthermore, researchers have been exploring the global application of the HSM crash prediction algorithm, hence transferability of CMFs to different road networks in other countries, such as Italy, Canada, Denmark, Germany, and New Zealand [36]. However, Gettman and Head found that traffic simulation platforms could be potential resources for evaluating vehicle interactions regarding safety aspects [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in (Sacchi, Persaud and Bassani, 2012), the logic of the physical Kalman regression model is used to set the expression for the measurement model according to the needs of the research problem, and does not develop a formal or comparative system Derivation. Of course, there are some scholars on the Kalman regression model for a more systematic derivation, it is these deduction greatly developed Kalman regression model in the application of economic science theoretical basis.…”
Section: Introductionmentioning
confidence: 99%
“…Though, only few researches performed an examination of transferability for safety analysis. Previous studies found out four more significant metrics (Al Kaaf & Abdel-Aty, 2015;Cafiso, Di Silvestro, & Di Guardo, 2012;Cunto et al, 2013;D'Agostino, 2014;Haas, 2015;Sacchi, Persaud, & Bassani, 2012;Waihrich, 2015;Washington, Persaud, Lyon, & Oh, 2005): (1) The R 2 can provide a measure of how well the observed crashes are likely to be predicted by the model. This metric was addressed in most studies due to its popularity and simplicity (Al Kaaf & Abdel-Aty, 2015;Cafiso et al, 2012;Cunto et al, 2013;D'Agostino, 2014;Silva, 2012;Waihrich, 2015).…”
Section: Crash Prediction Modelsmentioning
confidence: 99%
“…Most studies used Mean Absolute Deviation (MAD) as Goodness-of-fit (GOF) measure (Al Kaaf & Abdel-Aty, 2015;Cunto et al, 2013;Persaud, Saleem, Faisal, & Lyon, 2012;Sacchi et al, 2012;Waihrich, 2015). It differs from MAPE because it can consider segments where no crashes happened, which means observed values were equal to zero.…”
Section: Crash Prediction Modelsmentioning
confidence: 99%